Genetic impact of non-consanguineous marriages in Saudi Arabia. - Mohammed Alyahya; Taghrid Aloraini; Youseef Al-Harbi; Lamia Alsubaie; Abdulrahman Alswaid; Wafaa Eyaid; Fuad Al Mutairi; Faroug Ababneh; Majid Alfadhel; Ahmed Alfares (Journal of Biochemical and Clinical Genetics, 2022)
Background: Physicians and geneticists face challenges in making accurate diagnoses during clinical evaluations; affecting patients and clinicians. The aim of this study was to estimate the hit rate of the non-consanguineous population. Moreover, prevalence of the genetic disorder in both the consanguineous and non- consanguineous population of Saudi Arabia at King Abdulaziz Medical City in Riyadh data. Methods: We reviewed 681 families and 1563 individuals with 2,565,335 variants in the King Abdullah International Medical Research Center (KAIMRC) Genomic Database (KGD), Riyadh, Saudi Arabia. All the ES requests were obtained from the physician and clinical geneticist of KAIMRC, and the test was performed either in-house or in a College of American Pathologists accredited laboratory center for clinical purposes. Results: A total of 151 non-consanguineous individuals with exome sequencing requests in the population genomic database of King Abdullah International Medical Research Center was considered for the study. In total, 27 had disease-causing variants, and the hit rate was 27/151 (18%). Among the 28 different variants in the 27 individuals, 50% were de novo variants and 50% inherited. The hit rate of the variants causing autosomal recessive disorders was 12/28 (42.8%), autosomal dominant disorders 13/28 (46.4%), and X-linked disorders 3/28 (10.7%). Conclusion: Non-consanguineous marriages have a lower risk of genetic disorders, and reducing consanguinity reduces the risk of genetic disorders by two to three times. [JBCGenetics 2022; 5(2.000): 37-42]